2019
DOI: 10.48550/arxiv.1910.14051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cosmological Bootstrap: Weight-Shifting Operators and Scalar Seeds

Daniel Baumann,
Carlos Duaso Pueyo,
Austin Joyce
et al.

Abstract: A key insight of the bootstrap approach to cosmological correlations is the fact that all correlators of slow-roll inflation can be reduced to a unique building block-the four-point function of conformally coupled scalars, arising from the exchange of a massive scalar. Correlators corresponding to the exchange of particles with spin are then obtained by applying a spin-raising operator to the scalar-exchange solution. Similarly, the correlators of massless external fields can be derived by acting with a suitab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 55 publications
1
81
0
Order By: Relevance
“…Primordial tensor non-Gaussianities have been object of several studies and provide an interesting window to interactions taking place during inflation at very high energies [62,68,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. The galaxy shape field bispectrum g g g or cross-correlations of shape and density such as g g δ and g δ δ contain the direct information on tensor non-Gaussianities h h h and the respective cross-correlations with the scalar perturbation h h ζ and h ζ ζ through the modelling of how g ij responds to tensor perturbations we explained in Section 3.…”
Section: Tensor Non-gaussianities and Intrinsic Alignmentsmentioning
confidence: 99%
“…Primordial tensor non-Gaussianities have been object of several studies and provide an interesting window to interactions taking place during inflation at very high energies [62,68,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. The galaxy shape field bispectrum g g g or cross-correlations of shape and density such as g g δ and g δ δ contain the direct information on tensor non-Gaussianities h h h and the respective cross-correlations with the scalar perturbation h h ζ and h ζ ζ through the modelling of how g ij responds to tensor perturbations we explained in Section 3.…”
Section: Tensor Non-gaussianities and Intrinsic Alignmentsmentioning
confidence: 99%
“…Indeed, momentum space is the natural arena for many types of observables. Example contexts include cosmology [16][17][18][19][20][21][22][23][24][25][26], 'conformal collider' physics [27][28][29][30][31], anomalies [32][33][34][35], and quantum critical transport [36][37][38][39][40][41]. Momentum space is also useful for computing conformal blocks and the conformal bootstrap [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Related to this, we also noted that the purely single-sided correlator that displays maximal chaos can be interpreted as an inflationary correlator by moving all operators to the future boundary. It might therefore be possible to use the recent developments in the cosmological bootstrap [56][57][58][59] to directly write down the OTOC for arbitrary masses. If it can then be confirmed that the OTOC also displays maximal chaos for very light fields (such as the inflaton), one can study the implications of maximal chaos on inflation.…”
Section: Discussionmentioning
confidence: 99%